2022
DOI: 10.1101/2022.04.19.488643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Female behavior drives the formation of distinct social structures in C57BL/6J versus wild-derived outbred mice in field enclosures

Abstract: As an essential biomedical model organism, house mice have been studied intensely under laboratory conditions, yet they evolved to survive and reproduce in complex and dynamic environments. There has been recent interest in the study of "rewilded" mice reared in complex outdoor environments, particularly for understanding the brain and behavior. Yet little work has examined lab mouse behavior under free-living conditions. Here, we characterize the emergent spatial and social structure of replicated populations… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 166 publications
3
11
1
Order By: Relevance
“…Previous rewilding experiments have found that rewilding does produce increases in the magnitude of IL-17 production in response to antigenic stimuli, and this increase may be tied to the increase in granulocytes observed in rewilding and through exposure to commensal fungi, which generally provoke T helper (T H ) 17 cell differentiation (24,36). Given that IL-17RA mediates neuronal signaling for social behavior, there may be links between type 17 immunity, antigenic experience, and the behavioral variation among rewilded strains described here and observed by others (17). We might also particularly expect variation between lab-housed and rewilded mice in their degree of sociability because of their differences in IL-17 signaling (30).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Previous rewilding experiments have found that rewilding does produce increases in the magnitude of IL-17 production in response to antigenic stimuli, and this increase may be tied to the increase in granulocytes observed in rewilding and through exposure to commensal fungi, which generally provoke T helper (T H ) 17 cell differentiation (24,36). Given that IL-17RA mediates neuronal signaling for social behavior, there may be links between type 17 immunity, antigenic experience, and the behavioral variation among rewilded strains described here and observed by others (17). We might also particularly expect variation between lab-housed and rewilded mice in their degree of sociability because of their differences in IL-17 signaling (30).…”
Section: Discussionmentioning
confidence: 53%
“…Such patterns of association can shape the transmission and exchange of microbes and antigens, whether pathogenic (7,8) or nonpathogenic: For example, in the wild, microbiome similarity between individuals correlates with social group membership (9,10) and the strength of social and spatiotemporal network ties (11)(12)(13)(14). Social interactions are intimately linked to shared spatiotemporal movement patterns because patterns of movement will constrain who individuals interact with, which, in turn, feed back into patterns of movement (15)(16)(17). The two are often treated in the literature as somewhat synonymous, with association networks calculated from spatiotemporal co-occurrences frequently referred to as "social networks" in reflection of these feedbacks.…”
Section: Introductionmentioning
confidence: 99%
“…The trial design limits males' ability to escape the interaction. In natural environments males would likely avoid prolonged encounters [66], and dominance relationships would be established through shorter repeated interactions. Nevertheless, the sustained encounters used in this study allowed us to observe temporal shifts in fight intensity.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the enclosures at Cornell University's Liddell Field Station can be found elsewhere [39], so here we will only describe those elements critical to the success of this experiment. The enclosure is 15 × 38 m, approximately 9000 times the area of a typical mouse cage.…”
Section: Methodsmentioning
confidence: 99%
“…For social network analyses, we inferred the amount of time that animals overlapped in the same zone based on their patterns of RFID reads. We have described the process for inferring the duration of overlap elsewhere in detail [39]. Briefly, if a mouse registered consecutive RFID reads in the same zone within a given time window, we assume that the mouse had been in the zone for the period between those reads.…”
Section: Methodsmentioning
confidence: 99%